Defibrotide augments the anticandidial activity of NK cells - (:unkn) unknown (ELSEVIER SCIENCE INC, 1997)
1. The mechanism of action of Defibrotide, a fibrinolytic agent on Natural Killer (NK) cell cytotoxicity, was investigated through verapamil, TMB-8 cells and pertussis toxin. 2. Defibrotide increased the activity against Candida albicans cells (anticandidial activity), and it is determined that the calcium channels have a role in this effect. 3. Blockage of calcium channels reduced the anticandidial effect by 39.2%. Pertussis toxin led to a 10.7% inhibition, whereas the application of TMB-8 resulted in the stimulation of anticandidial activity. 4. It is concluded that defibrotide is a potent activator of NK cells. (C) 1997 Elsevier Science Inc.
Keywords: NATURAL-KILLER-CELLS; INVIVO; MARROW